2001
DOI: 10.4049/jimmunol.166.5.3052
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface-Expressed Moesin-Like Receptor Regulates T Cell Interactions with Tissue Components and Binds an Adhesion-Modulating IL-2 Peptide Generated by Elastase

Abstract: The adhesion of leukocytes to the extracellular matrix (ECM) depends on their responses to variations in the chemotactic signals in their milieu, as well as on the functioning of cytoskeletal and context-specific receptors. Ezrin, radixin, and moesin constitute a family of proteins that link the plasma membrane to the actin cytoskeleton. The surface expression of moesin on T cells and its role in cell adhesion has not been fully elucidated. Recently, we found that IL-2 peptides generated by elastase modified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…This membranelinking protein is expressed by various blood cells including megakaryocytes and granulocytes (23), but its expression was thought to be localized inside the cell membrane and not on the cell surface. Some studies revealed that anti-moesin Abs could bind to the surface of T cells (18) and macrophages (19) in keeping with our observation. However, none of the previous studies characterized the cell surface protein recognized by the anti-moesin Abs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This membranelinking protein is expressed by various blood cells including megakaryocytes and granulocytes (23), but its expression was thought to be localized inside the cell membrane and not on the cell surface. Some studies revealed that anti-moesin Abs could bind to the surface of T cells (18) and macrophages (19) in keeping with our observation. However, none of the previous studies characterized the cell surface protein recognized by the anti-moesin Abs.…”
Section: Discussionsupporting
confidence: 92%
“…Moesin is an intracellular protein that links the cell membrane and cytoskeleton, and mediates the formation of microtubules and cell adhesion sites as well as ruffling of the cell membrane (17). On the other hand, some reports have identified molecules that were recognized by anti-moesin mAbs on the surface of blood cells such as T cells and macrophages (18,19). Because these immune cells are an important source of myelosuppressive cytokines such as TNF-␣ and IFN-␥, it is conceivable that anti-moesin Abs in AA patients may bind such moesin-like molecules on these immune cells and affect the cytokine secretion from these cells.…”
mentioning
confidence: 99%
“…Although moesin has a cell surface domain involved in the binding of lipopolysaccharides (21), IL-2 fragments (22), and human immunodeficiency virus type 1 envelope protein gp 120 (23), moesin has no signal peptide, is not expressed on the cell surface, and is not a GPI-anchored type protein. In this study, we demonstrated that the newly purified apoA-I/HDL binding protein is expressed on the cell surface, exclusively on macrophages, and is a GPIanchored type.…”
Section: Discussionmentioning
confidence: 99%
“…In areas of inflammation, Masumoto et al (26) has shown moesin to be expressed in both the center and periphery of neutrophils. Moesin has been reported to have diverse biological functional activities, ranging from a structural protein to a receptor (5,16,37,40,47,51).…”
mentioning
confidence: 99%